Cyclotribenzoin - Ji, Qing; Do, Loi H.; Miljanić, Ognjen Š. (Synlett, 2015)
Using cyanide-assisted benzoin condensation of isophthaldehyde, we prepared cyclotribenzoin: a cone-shaped macrocycle whose three benzene rings define a cuplike cavity, while six of its C–H bonds convergently point in the opposite direction. This combination of convergently oriented cation- and anion-binding groups, coupled with an exceedingly simple synthesis, promises to make cyclotribenzoin an appealing platform for supramolecular chemistry studies.
Keywords: condensation; macrocycles; host–guest systems; molecular recognition; supramolecular chemistry